The Sinclair Effect: Comparing Ownership Influences on Bias in Local TV News Content. Issue 3 (3rd July 2019) - Hedding, Kylah J.; Miller, Kaitlin C.; Abdenour, Jesse; Blankenship, Justin C.
Abstract : Sinclair Broadcast Group, the largest owner of U.S. local television stations, has received recent attention due to its apparent political lean and journalistic practices. This study compared the content and quality of national political news stories at Sinclair and non-Sinclair stations in three television markets. Results indicated evidence of a "Sinclair Effect, " whereby Sinclair-owned affiliate stories exhibited more cable news-style elements. Stations generally adhered to traditional journalistic principles, regardless of ownership, but Sinclair stations produced more stories with dramatic elements, commentary, and partisan sources.